Body size determines soil community assembly in a tropical forest. Issue 3 (22nd November 2018) - Zinger, Lucie; Taberlet, Pierre; Schimann, Heidy; Bonin, Aurélie; Boyer, Frédéric; De Barba, Marta; Gaucher, Philippe; Gielly, Ludovic; Giguet‐Covex, Charline; Iribar, Amaia; Réjou‐Méchain, Maxime; Rayé, Gilles; et al.
Abstract: Tropical forests shelter an unparalleled biological diversity. The relative influence of environmental selection (i.e., abiotic conditions, biotic interactions) and stochastic–distance‐dependent neutral processes (i.e., demography, dispersal) in shaping communities has been extensively studied for various organisms, but has rarely been explored across a large range of body sizes, in particular in soil environments. We built a detailed census of the whole soil biota in a 12‐ha tropical forest plot using soil DNA metabarcoding. We show that the distribution of 19 taxonomic groups (ranging from microbes to mesofauna) is primarily stochastic, suggesting that neutral processes are prominent drivers of the assembly of these communities at this scale. We also identify aluminium, topography and plant species identity as weak, yet significant drivers of soil richness and community composition of bacteria, protists and to a lesser extent fungi. Finally, we show that body size, which determines the scale at which an organism perceives its environment, predicted the community assembly across taxonomic groups, with soil mesofauna assemblages being more stochastic than microbial ones. These results suggest that the relative contribution of neutral processes and environmental selection to community assembly directly depends on body size. Body size is hence an important determinant of community assembly rules at the scale of the ecological community in tropical soils and should be accounted for in spatial models of tropical soil food webs. Abstract : see also the Perspective by Dumbrell